Effects of Child-Centered Play Therapy on social-emotional development of refugee children with anxiety in Kuala Lumpur, Malaysia - Taheri, Melika (2017)
This case study explored the effect of Child-Centered Play Therapy (CCPT) on the social-emotional development of nine refugee children with anxiety in Kuala lumpur, Malaysia. Refugee children are not a homogenous group but have group-specific and individual needs. Therefore, to have a homogenous group, Farsi-speaker refugee children with anxiety between the ages of 8 to 12 years from both gender in Kuala lumpur, Malaysia were selected as purposive sample. These children as referral cases went through screening process in the first step. The Spence Children’s Anxiety Scale (SCAS) was utilized as an instrument to screen anxiety in referral cases through preintervention to have a group with a similar characteristics. To meet the objectives of study, these children participated in 10 sequence weekly individual CCPT sessions in the Sahabat Centre play therapy counseling room. During this study, the therapeutic process based on the social-emotional development of children was the focus point. In CCPT sessions, the Landreth method were followed which contained the role of children as the leaders and the role of play-therapist as a facilitator to support and accept children with positive regard to provide supportive environment which helped children to meet their needs. Through the total ninety CCPT sessions, data were collected on each child’s therapeutic session via individual participant observation of the researcher, field- notes, video recording and photos taking, alongside participants’ weekly journal entries. Supervision over the process of data collection by a professional reviewer took place to evaluate the process step by step. Data were analyzed manually via axial coding. The participants’ shared inner feelings and experiences in CCPT process from the refugee children’s journal entries answered the first objective. The analyzed data from other techniques such as participant’s observation covered the second objective. Finally, the general objective revealed positive progress of participants in the social-emotional development areas such as emotional-recognition and emotional-regulation, and also positive relationship with others. In this process the self-development were highlighted as an unavoidable portion of development. Participants revealed progress in self-development area such as self-acceptance and independency. The final result indicated that CCPT was an effective intervention for this small sample of refugee children. Furthermore, the theoretical and the practical implications were defined as well so the final outcome were aligned with the Erik Erikson psychosocial theory focused on industry versus inferiority stage and also the CCPT by believing in participants inner resources to resolve their own conflicts. The outcome of study highlighted the healing process as a key point in participants’ journey and this study suggested to give greater look into the vulnerable group while considering effective suitable developmental methods.